Examining fall risk among formerly homeless older adults living in permanent supportive housing. (9th December 2019) - Henwood, Benjamin F.; Rhoades, Harmony; Lahey, John; Pynoos, Jon; Pitts, Deborah B.; Brown, Rebecca T.
Abstract: Although permanent supportive housing (PSH) has been credited with a decline in the number of chronically homeless adults in the United States since 2007, the extent to which PSH can accommodate the needs of a prematurely aging population, including reducing the likelihood of falls, is unclear. The objective of this study is to examine the prevalence and correlates of falls with a sample of 237 tenants (45‐ to 80‐year olds) from two PSH programmes in Los Angeles from 1 January 2017 to 10 August 2017. We also explore the location and severity of fall‐related injury using a subsample of 66 tenants. Standard surveys queried demographics, health status, history of homelessness and falls. Multivariable logistic regression assessed the correlates of falling in the past year. More than half of the sample had fallen and more than 40% had multiple falls in the past year. Functional impairment, frailty and persistent pain were all associated with increased fall risk. For the 66 tenants who provided more detailed fall information, more than 40% fell at home and of those nearly half fell in their bathroom. Fall‐related injuries were common, with more than one‐third of the subsample experiencing serious injury. These findings suggest that fall prevention is needed in PSH but that more research is needed to understand the degree to which individual and environmental risk factors are contributing to falls.